Impact of preoperative patient education on the prevention of postoperative complications after major visceral surgery: the cluster randomized controlled PEDUCAT trial - Ulla Klaiber; Lisa M. Stephan-Paulsen; Thomas Bruckner; Gisela Müller; Silke Auer; Ingrid Farrenkopf; Christine Fink; Colette Dörr-Harim; Markus K. Diener; Markus W. Büchler; Phillip Knebel (Trials, 2018)
Abstract Background The prevention of postoperative complications is of prime importance after complex elective abdominal operations. Preoperative patient education may prevent postoperative complications and improve patients’ wellbeing, but evidence for its efficacy is poor. The aims of the PEDUCAT trial were (a) to assess the impact of preoperative patient education on postoperative complications and patient-reported outcomes in patients scheduled for elective complex visceral surgery and (b) to evaluate the feasibility of cluster randomization in this setting. Methods Adult patients (age ≥ 18 years) scheduled for elective major visceral surgery were randomly assigned in clusters to attend a preoperative education seminar or to the control group receiving the department’s standard care. Outcome measures were the postoperative complications pneumonia, deep vein thrombosis (DVT), pulmonary embolism, burst abdomen, and in-hospital fall, together with patient-reported outcomes (postoperative pain, anxiety and depression, patient satisfaction, quality of life), length of hospital stay (LOS), and postoperative mortality within 30 days after the index operation. Statistical analysis was primarily by intention to treat. Results In total 244 patients (60 clusters) were finally included (intervention group 138 patients; control group 106 patients). Allocation of hospital wards instead of individual patients facilitated study conduct and reduced confusion about group assignment. In the intervention and control groups respectively, pneumonia occurred in 7.4% versus 8.3% (p = 0.807), pulmonary embolism in 1.6% versus 1.0% (p = 0.707), burst abdomen in 4.2% versus 1.0% (p = 0.165), and in-hospital falls in 0.0% versus 4.2% of patients (p = 0.024). DVT did not occur in any of the patients. Mortality rates (1.4% versus 1.9%, p = 0.790) and LOS (14.2 (+/− 12.0) days versus 16.1 (+/− 15.0) days, p = 0.285) were also similar in the intervention and control groups. Conclusions Cluster randomization was feasible in the setting of preoperative patient education and reduced the risk of contamination effects. The results of this trial indicate good postoperative outcomes in patients undergoing major visceral surgery without superiority of preoperative patient education compared to standard patient care at a high-volume center. However, preoperative patient education is a helpful instrument not only for teaching patients but also for training the nursing staff. Trial registration German Clinical Trials Registry, DRKS00004226. Registered on 23 October 2012. Registered 8 days after the first enrollment.